2017
DOI: 10.1158/1055-9965.epi-16-0882
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Volumetric Breast Density with Tamoxifen and Aromatase Inhibitors

Abstract: Background Reductions in breast density with tamoxifen and aromatase inhibitors may be an intermediate marker of treatment response. We compare changes in volumetric breast density among breast cancer cases using tamoxifen or aromatase inhibitors (AI) to untreated women without breast cancer. Materials and Methods Breast cancer cases with a digital mammogram prior to diagnosis and after initiation of tamoxifen (n=366) or AI (n=403), and a sample of controls (n=2170) were identified from the Mayo Clinic Mammo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 31 publications
3
27
2
Order By: Relevance
“…Small changes in density in the SMART trials might have been missed with the Cumulus semiautomated method if baseline density is low, as is often the case in postmenopausal women (25). Change in FGV volume after 6 months of Duavee (median total for both breasts of À12 cm 3 or À6 cm 3 /per breast) in our pilot is in the range of the annual change in FGV of À8 cm 3 over an average of 3 years in contralateral breasts for premenopausal women with breast cancer taking tamoxifen (42). In addition to breast cancer risk, endogenous levels of progesterone in postmenopausal women have been reported as positively correlated with percent mammographically dense area (43).…”
Section: Discussionmentioning
confidence: 75%
“…Small changes in density in the SMART trials might have been missed with the Cumulus semiautomated method if baseline density is low, as is often the case in postmenopausal women (25). Change in FGV volume after 6 months of Duavee (median total for both breasts of À12 cm 3 or À6 cm 3 /per breast) in our pilot is in the range of the annual change in FGV of À8 cm 3 over an average of 3 years in contralateral breasts for premenopausal women with breast cancer taking tamoxifen (42). In addition to breast cancer risk, endogenous levels of progesterone in postmenopausal women have been reported as positively correlated with percent mammographically dense area (43).…”
Section: Discussionmentioning
confidence: 75%
“…At least one small study has correlated the likelihood of breast cancer recurrence after adjuvant tamoxifen with reductions in MRI FGV, finding that PMD reduction on tamoxifen was the only independent factor associated with recurrence; mean reduction was around 20% in the group without recurrence and only 2-6% in the group with recurrence (235). in dense volume and VBD in cases compared to controls using Volpara and Quantra; reductions were greatest when baseline VBD was more than 10% (236). Concerning other SERMs such as raloxifene, and AIs, the data for the use of MD as a biomarker is less robust and reported reductions in MD appear to be less and very heterogeneous.…”
Section: As a Biomarker For Clinical Interventionsmentioning
confidence: 99%
“…These measures were obtained on different scales and therefore comparisons are difficult. A recent observational study in breast cancer patients showed an association between endocrine therapies and reduction on digitally obtained volumetric breast density (53) but no data are available so far, on the magnitude of the effect with a prognostic significance.…”
Section: Discussionmentioning
confidence: 99%